Leadership Special Issue: Do we need Authentic Leadership? Interrogating authenticity in a new world order. (August 2021) - Iszatt-White, Marian; Carroll, Brigid; Gardiner, Rita A; Kempster, Steve
Authentic Leadership (AL) has been claimed as the 'root construct' (Avolio and Gardner, 2005) for other forms of 'aspirational' leadership with underpinnings in positive psychology. It has also been explicitly positioned as a response to the 'ethical corporate meltdown' (May et al., 2003: 247) said to have resulted from previous forms of leadership. Yet it has struggled to live up to its acknowledged functionalist and instrumentalist aims. At the same time, AL has proved resistant to important philosophical challenges seeking to problematize the nature of the 'true self' and draw attention to the complexities of enacting authenticity in the daily practice of leadership. These ambitious claims and unaddressed issues are at the heart of this special issue's enquiry as to whether AL is fit for purpose as a driver of leadership theory and practice in the current world order, and its call for more critical attention to be paid to the notion of authenticity in leadership. The contributions to this special issue blend traditional, empirical papers with invited 'Leading Questions' thought pieces to offer a fundamental interrogation of authenticity at the same time as achieving a balance of perspectives.